The role of the KRSIK motif of human angiogenin in heparin and DNA binding. Issue 86 (31st August 2016) - Yeo, Kwon Joo; Jee, Jun-Goo; Park, Jin-Wan; Lee, Yu-Jin; Ryu, Kyoung-Seok; Kwon, Byoung-Mog; Jeon, Young Ho; Cheong, Hae-Kap
Abstract : The 50 KRSIK 54 motif is the main interaction site of hAng for heparin and DNA binding, providing an insight into the potential role of the motif for the internalization and DNA binding of hAng, which is essential for the regulation of angiogenesis. Abstract : The positively charged surface with a 50 KRSIK 54 motif is the main interaction site of hAng for both heparin and DNA binding, providing an insight into the potential role of the 50 KRSIK 54 motif for the internalization and promoter binding of hAng, which is essential for the regulation of angiogenesis.